Sleep-disordered breathing in elderly people and subjective sleep-wake disturbance - Mant, A; Eyland, E A; Hewitt, H; Fox, M; Goode, E; LeCount, A; Pond, D; Saunders, N A (Age and ageing, 1992)
Sleep-disordered breathing and subjective reports of sleep-wake disturbances are both common in elderly people but previous studies investigating the relationship between the two have produced uncertain results. We hypothesized that there is no relationship between sleep-disordered breathing and subjective reports of sleep-wake disturbance. Ninety-three random-sampled retirement-village residents, mean age 77.6 years, were monitored overnight with a portable microprocessor-based system. The respiratory disturbance index (RDI) was used as a measure of sleep-disordered breathing. Subjects were interviewed regarding sleep-wake patterns and snoring history and the Mini Mental State Examination, Geriatric Depression Scale and Nelson Adult Reading Test were administered. The sleep-wake responses were entered into a principal components analysis. Two components, reflecting night-time and daytime disturbance, accounted for 34% of the variance. Multiple regression analyses were performed using RDI as a continuous dependent variable, and three predictor variables, night-time, and daytime disturbance and history of snoring. Together, these variables accounted for only 2% of the variance. We conclude there is no relationship between mild and moderate sleep-disordered breathing and subjective sleep-wake disturbance in this population.